Exploring Common Errors in Using Passive Voice Made by EFL (English Foreign Language) Learners’ - Alfi Najah; Moh Zainuddin; Iin Widya Lestari; Alfi Najah; Moh Zainuddin; Iin Widya Lestari (INTENS (International Journal of English Education and Linguistics), 2024)
In grammar class, beside on learner score result which learners still confused and make mistake in using passive voice. Dealing the phenomena researcher done research to findout the common error and the factors errors that made by learners in using passive voice. If errors are allowed to persist, it can cause errors fossilize. This research used descriptive qualitative research method and learner at second grade of English education department as participant. The researcher conducted three type test and interview as collecting data. The researcher conclude that Be is the highest percentage errors type on three type tests with error on test type one 50% and test type three 40%. Then omission with error percentage type one 31% and type three 37%, Verb 3 with type one 9% and type two 52% errors, Verb 1 with error 43%, Subject/Object with type one 9% and type three 23%, and the lowest error was Verb-ing with error percentage 5%. Researcher conclude that the factor errors made by learner such as Verb 3, Omission, and Be, it was a carelessness. Learners understand about material test but still make error like uncomplete sentences (miss to be), those was mean carelessness.